Origin of Meteoric Fluids in Extensional Detachments - Paul D. Bons; Enrique Gomez-Rivas (Geofluids)
Minerals in veins and shear zones often show oxygen and hydrogen isotope ratios that are interpreted as recording interaction with meteoric water, at depths up to about 10 km. Downward fluid flow to these depths can only occur in the unlikely case of fluid pressures that are significantly lower than lithostatic overburden pressures. We therefore propose that fluid movement was upward instead of downward. In our model, the pore space within sediments and exhumed rocks below an unconformity is filled with meteoric and possibly seawater fluids. Burial of these rocks traps the fluids that can retain their meteoric isotopic composition as long as temperatures remain below about 300-350°C. Extension or rapid exhumation, such as that experienced by metamorphic core complexes, which results in decompression or fluid heating can release these old “meteoric” fluids, of which we find the isotopic fingerprint in veins and shear zone minerals.